The use of complex decongestive therapy in the process of rehabilitation in the case of primary and secondary lymphatic insufficiency - Wilczyńska, Agnieszka; Wawryków, Agata; Korabiusz, Katarzyna; Niedzielska, Mirela; Janik, Inga; Fabian-Danielewska, Anna; Maciejewska, Martyna; Gutowski, Piotr (Journal of Education, Health and Sport, 2018)
The purpose of this study is to draw attention to the problems connected with the failure of the lymphatic system. In particular the primary and secondary swelling. The reference in this work to the scientific literature indicates a growing need for the development of Lymphology in Poland. It indicates a significant problem, which is the lack of specific standards and procedures of treatment and methods of treatment of disorders of lymph in the educational process of medical schools in Poland.